The Effect of Training and Non-Physical Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable - Muhammad Bagus Sadewo; Wawan Prahiawan; Emma Suryani (Institute of Advanced Knowledge and Science, 2025)
This study aims to determine the extent of influence of Training and Non-Physical Work Environment on Employee Performance and the role of Job Satisfaction as a mediating variable at Cileungsi Regional General Hospital, Bogor Regency. The research method used is a quantitative method with the population used being all nurses at Cileungsi Regional General Hospital totaling 215 people, with a sample size of 100 people. Sampling using the saturated sample method. Data collection techniques used are observation, interviews and questionnaires. The data obtained in this study were through respondents, sources, and literature studies. The data analysis method used is PLS (Smart Partial Least Square). The results of this study indicate that: Training has a negative and insignificant effect on Employee Performance. Non-Physical Work Environment has a positive and significant effect on Employee Performance. Training has a positive and significant effect on Job Satisfaction. Non-Physical Work Environment has a positive and significant effect on Job Satisfaction. (5) Job Satisfaction has a positive and significant effect on Employee Performance. Job Satisfaction is able to mediate the relationship between Training and Employee Performance. Job Satisfaction is able to mediate the relationship between Non-Physical Work Environment and Employee Performance.